Ferramenta SWAT para modelagem hidrológica na área da bacia do Ribeirão Cafezal em Londrina - PR - Kataoka, Fábio Eidi (2017)
The modeling of environmental studies encompasses several areas of the natural sciences, with emphasis on water resources, since the same refers to the simulation of hydrossedimentological events that have relationships with soil associated with waterproofing of soils. Thus, information that is attributed to accuracy in the decision-making processes are very important subsidies, based on the premise that a modeling can aid in the reproduction of scenarios that serve as future predictions. The present work aims to simulate a flow in the upper part of the Ribeirão Cafezal basin, located in the cities of Rolândia, Cambé and Londrina, Paraná, through the SWAT (Soil and Water Assessment Tool). The model requires the cartographic characterization of the study area, which includes data on land use and cover, pedology and topography, as well as climatological information on precipitation, wind, humidity, temperature and solar radiation. The methodological steps consisted of: 1 - Data acquisition and entry without SWAT database; 2 - Definition of the sub-basins and the Hydrological Response Units (HRU); 3 - Sensitivity analysis; 4 - Calibration of the model; 5 - Simulation and 6 - Validation of the model. Using the simulated void results methodology in the year 2004, they were calibrated and compared to the flow rate observed in a fluviometric station of the ANA (Agência Nacional das Águas), located non-exuded in the studied basin, thus obtaining a sum of the squares of the residuals of 0,17 and a good representation of the general tendency of the flow. Subsequently with the calibrated parameters, the data were validated with the year 2005, obtaining the result of the sum of the squares of the residues of 0.46, these results are not very satisfactory for the period of validity. In general, and with available information available, it is possible to visualize a very useful tool for simulation and management of water resources.